Validity of severity of dependence scale-Indonesia in patients with drug and alcohol dependence - Kusumadewi, Andrian Fajar; Andina, Jennifer; Sihageng, Hermanuaji; Putra, Muhammad Jordan Diandra (Intelektual Pustaka Media Utama, 2024)
A quick and self-administrative screening tool to detect dependence on various substances is vital in the early detection of multiple substance dependence. This study aimed to validate the severity of the dependence scale Indonesian version (SDS-Ina) in a sample of clinically diagnosed substance-related disorder subjects. The study was an observational study and rapid assessment of suspected patients with drug and alcohol dependence in an outpatient psychiatric unit in Yogyakarta, Indonesia. The translated severity of dependence scale-Indonesia (SDS-Ina) questionnaire was given out to 65 subjects through an online form. The content validity of the translated SDS was assessed with Aiken’s V, and concurrent validity was analyzed in comparison to the Diagnostic of Statistical and Manual Mental Disorder IV (DSM-IV) diagnosis criteria with Pearson correlation coefficient and factor validity through principal component analysis (PCA). Reliability was assessed using Cronbach’s Alpha and test-retest reliability. Aiken’s V index concluded that our content validity was valid (all>0.75). A Pearson correlation coefficient of=0.93 (P<0.001), PCA of all items ≥0.60 further validates the SDS-Ina. Internal reliability of Cronbach’s Alpha 0.907 and test-retest reliability (intraclass correlation coefficient (ICC): all≥0.75). In conclusion, the translated SDS is a valid and reliable tool to measure the psychological dependence of Indonesian subjects involved in this study.